Eco Kids, Ano 2, Número 3, Agosto de 2010, Ilhéus/BA - (:unkn) unknown (Ministério Público do Estado da Bahia, 2010)
No abstract.
Keywords: Educação ambiental; Meio Ambiente; Plástico biodegradável; Reciclagem; CNPQ::CIENCIAS SOCIAIS APLICADAS::DIREITO